2015
DOI: 10.1089/neu.2015.3947
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Risk for Central Pain Using the Sensory Components of the International Standards for Neurological Classification of Spinal Cord Injury

Abstract: Central neuropathic pain (CP) after spinal cord injury (SCI) is excruciating and difficult to manage. Pre-emptive treatment could be initiated in patients at risk for CP providing that it can be predicted. A combination of psychophysical tests could predict CP, but the process necessitates sophisticated equipment and constant monitoring. A simple predictive tool for CP is required. The aim of this study was to test the predictability for CP of the sensory component of the International Standards for Neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Interestingly, the CNP characteristics did not correlate with SCI characteristics including level of injury, AIS score and cause of injury. This finding is in agreement with previous studies [27,55,56]. The finding further support the role of the psychological sequel of SCI, or alternatively the psychological predisposition, in the emergence and perhaps in the chronification of CNP.…”
Section: Discussion Increased Ptsd and Psychological Distress In Cnpsupporting
confidence: 93%
“…Interestingly, the CNP characteristics did not correlate with SCI characteristics including level of injury, AIS score and cause of injury. This finding is in agreement with previous studies [27,55,56]. The finding further support the role of the psychological sequel of SCI, or alternatively the psychological predisposition, in the emergence and perhaps in the chronification of CNP.…”
Section: Discussion Increased Ptsd and Psychological Distress In Cnpsupporting
confidence: 93%
“…This theory is supported by studies finding a correlation between evoked at-level pain and ongoing below-level pain. [70][71][72] Further studies that carefully assess various symptoms of SCI and their changes over time and a better understanding of the translation of behavioral correlates of pain and spasticity from animals to humans and back are needed in order to further understand how various changes in interdependent neuronal networks can result in different symptoms and signs.…”
Section: Identifying Mechanisms That Neuropathic Pain and Spasticity mentioning
confidence: 99%
“…One limitation of this assessment is that dermatomes that have either decreased sensation or are hypersensitive fall into to the same category of impaired sensation. Only a few studies looked at the relation between the ISNCSCI sensory measures and the development of NP [42,43]. Hari et al found that patients that suffer from NP have enhanced sensory recovery measured by pinprick sensation in comparison to SCI patients that do not develop NP [42].…”
Section: 1 Behavioral Assessmentsmentioning
confidence: 99%
“…Hari et al found that patients that suffer from NP have enhanced sensory recovery measured by pinprick sensation in comparison to SCI patients that do not develop NP [42]. Another study found that lower at-level pinprick scores were more predictive than light touch scores for NP development [43]. …”
Section: 1 Behavioral Assessmentsmentioning
confidence: 99%